Incidence, Abundance and Damage of Papaya Mealybug In Southern Part of Bangladesh And Its Management (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The papaya mealybug, Paracoccus marginatus Williams and Granara de Willink, is a small hemipteran that attacks several genera of host plants, including economically important tropical fruits and ornamentals. A study was carried out at farmers’ papaya garden and homestead areas of 8 locations viz., Dumki, Bouphal, Dashmina, Patuakhali, Mirjagonj, Amtali, Kalapara and Kuakata of Patuakhali and Barguna districts of Bangladesh to observe the incidence, abundance, and damage potential of papaya mealybug, Paracoccus marginatus (Williams and Granara de Willink) from March to June 2019. An experiment consisting of seven treatments following randomized complete block design (RCBD) with three replications was conducted for controlling papaya mealybugs at Patuakhali Science and Technology University (PSTU) campus during March to June 2019. Results revealed that among 8 locations, the highest incidence of P. marginatus was recorded in June, and the lowest was in April. The maximum abundance of P. marginatus on leaves and fruits of the papaya plant was observed at Kolapara, and the lowest was at Amtali. The highest percent infested plants (65%) per location, infested leaves/plant (97%), and infested fruits/plant (47%) was recorded in Kolapara, and the lowest percent infestations (31, 18, and 11%, respectively) were in Amtali. Among all treatments, the removal of infested leaves with petioles and application of Nitro 505EC @ 1 ml/L of water (T1) was the best approach for the management of papaya mealybugs. The removal of infested leaves with petioles + Biotap plus extra 95EC @ 0.2 g/L of water (T3) could be used as 2nd choice for controlling papaya mealybugs. The results concluded that removal of infested leaves and the application of Nitro 505 EC at the rate of 1 ml/L of water might be used to control the papaya mealybug.J. Asiat. Soc. Bangladesh, Sci. 47(2): 109-120, December 2021